2018
DOI: 10.1186/s40246-018-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Linking a role of lncRNAs (long non-coding RNAs) with insulin resistance, accelerated senescence, and inflammation in patients with type 2 diabetes

Abstract: BackgroundStudying epigenetics is expected to provide precious information on how environmental factors contribute to type 2 diabetes mellitus (T2DM) at the genomic level. With the progress of the whole-genome resequencing efforts, it is now known that 75–90% of the human genome was transcribed to generate a series of long non-coding RNAs (lncRNAs). While lncRNAs are gaining widespread attention as potential and robust biomarkers in the genesis as well as progression of several disease states, their clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 58 publications
8
134
0
Order By: Relevance
“…ROC curve analysis revealed that the optimal cut-off value to distinguish DM from healthy control is ≤10 ng/µL, which would achieve a sensitivity of 85.1% and specificity of 67.3%, proving that circulating GAS5 is a good candidate for screening for diabetes. However, inconsistent results were found in another study focusing on lncRNAs from peripheral blood mononuclear cells (PBMCs) in which the level of GAS5 was upregulated, along with HOTAIR, MALAT1, and X-inactive specific transcript (XIST) [101]. Downregulation of GAS5 has also been implicated in polycystic ovary syndrome (PCOS), which is a disease tightly connected with insulin resistance and inflammation pathogenesis, comparable to DM.…”
Section: Gas5mentioning
confidence: 99%
“…ROC curve analysis revealed that the optimal cut-off value to distinguish DM from healthy control is ≤10 ng/µL, which would achieve a sensitivity of 85.1% and specificity of 67.3%, proving that circulating GAS5 is a good candidate for screening for diabetes. However, inconsistent results were found in another study focusing on lncRNAs from peripheral blood mononuclear cells (PBMCs) in which the level of GAS5 was upregulated, along with HOTAIR, MALAT1, and X-inactive specific transcript (XIST) [101]. Downregulation of GAS5 has also been implicated in polycystic ovary syndrome (PCOS), which is a disease tightly connected with insulin resistance and inflammation pathogenesis, comparable to DM.…”
Section: Gas5mentioning
confidence: 99%
“…In a recent study of 44,168 individuals, investigating a new risk profile for all-cause mortality increased blood glucose levels had a strong influence to all-cause mortality 60 . The concept of insulin excess as a promotor of accelerated aging is also supported by a study in Asian Indians where Satishkumar et al found an association between, insulin resistance, inflammation and cellular senescence 61 . These results have led to the hypothesis that RTL might be a biomarker of cellular senescence and predict CVD 62 .…”
Section: Discussionmentioning
confidence: 85%
“…Evidence has shown the implication of lnc-ANRIL in diabetes-related inflammation, transcriptional markers senescence, insulin resistance, etc. [20]. In diabetic complications including DN, diabetic cardiomyopathy and diabetic retinopathy, lnc-ANRIL has been observed to regulate the production of ECM proteins and vasoactive factors.…”
Section: Discussionmentioning
confidence: 99%